All the Mamas - Shough, Carol Gandee (Columbia, S.C. : Summerhouse Press, 1998)
Based on genealogical records from one family, this story briefly recounts historical events as experienced by generations of mothers and the daughters they loved and cared for.
Keywords: Mothers and daughters -- Fiction